Peningkatan Kompetensi Pedagogik Guru Bahasa Indonesia Melalui Pelatihan Model ADDIE dalam Mengimplemetasikan Pembelajaran Mendalam - Susilawati*, Imas; Rusyana, Yus; Ristiani, Iis (Universitas Suryakancana, 2026)
This article aims to describe the improvement in the pedagogical skills of Indonesian language teachers through ADDIE training in implementing in-depth learning in assisted schools. The method used was an explanatory sequential experimental design, with a sample of 20 teachers (10 in the experimental group, 10 in the control group) in Cianjur Regency. Data were collected through tests, questionnaires, interviews, and observations. The ADDIE training was conducted over five days, encompassing needs analysis, design, development, implementation, and evaluation. The experimental group's results showed a significant improvement (mean post-test score of 88, p < 0.05) compared to the control group, with teachers able to design contextual and enjoyable learning. Educational institutions need to provide digital resources and increase the frequency of mentoring to support the sustainability of the training, as well as examine the long-term impact on student achievement.Keywords: competence; pedagogy; training; in-depth learning Abstrak Artikel ini bertujuan mendeskripsikan peningkatan kemampuan pedagogik guru bahasa Indonesia melalui pelatihan model ADDIE dalam mengimplementasikan pembelajaran mendalam di sekolah dampingan. Metode yang digunakan desain eksperimen sekuensial eksplanatori dengan 20 guru sebagai sampel (10 kelompok eksperimen, 10 kelompok kontrol) di Kabupaten Cianjur. Data dikumpulkan melalui tes, kuesioner, wawancara, dan observasi. Pelatihan ADDIE dilaksanakan selama lima hari, mencakup analisis kebutuhan, desain, pengembangan, implementasi, dan evaluasi. Hasil kelompok eksperimen menunjukkan peningkatan signifikan (rata-rata skor post-test 88, p < 0.05) dibandingkan kelompok kontrol, dengan guru mampu merancang pembelajaran yang kontekstual dan menyenangkan. Institusi pendidikan perlu menyediakan sumber daya digital dan meningkatkan frekuensi pendampingan untuk mendukung keberlanjutan pelatihan, serta meneliti dampak jangka panjang terhadap prestasi siswa.Kata kunci: kompetensi; pedagogik; pelatihan; pembelajaran mendalam